Analisis Sektor Unggulan Dalam Pembangunan Wilayah Di Kabupaten Ogan Ilir - Hala Haidir (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
Regional development and national development are interrelated with each other, where the national development target in Indonesia is to create economic growth and equalize development results, including income distribution between regions. The concept of the leading sector economy explains that all economic activities that fall into two parts are basic and non-basic. The basis or superiority is an activity of a group that produces results in the form of services or goods that aim to send far out of the group's area, either regionally, within the country, or abroad. Ogan Ilir Regency is one of the areas in South Sumatra Province which has various sectors where the average economic growth rate during 2013- 2017 is 5.34% (BPS, 2018) with a growth rate, so the researcher aims to analyze the leading sectors in the regional development of Ogan Ilir Regency, it is hoped that it can provide important information about the base sector that can be the mainstay of Ogan Ilir Regency so that regional planning can be carried out in accordance with the potential development of superior commodities obtained. The method used is quantitative analysis: the rate of economic growth, LQ analysis to determine the basis and non-base leading sectors, and shiftshare analysis to identify the superior regional sectors by comparing them with larger regions (regional or national). The results obtained are that there are 7 of the 17 sectors that are the basis, and Based on the results of the ShiftShare calculation there are 4 (four) slow moving sectors, namely; 1) Agriculture, Forestry, and Fisheries; 2) Mining and Quarrying; 3) Financial and Insurance Services; and 4) Other Services. Meanwhile, 13 (thirteen) other sectors are moving progressively. Kata Kunci : Regional Development, Leading Sector, economic